The Legal Protection for The Parties Due to The Issuance of Overlapping Land Certificates (Decision Study Number: 1 K/PDT/2021) - Ayu Sri Adinda, I Gusti; Kurniawan, I Gede Agus (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2024)
The agrarian conflicts have increased in Indonesia throughout 2022, there have been 497 cases of criminalization of agrarian conflicts, namely land disputes experienced by land rights fighters in various parts of the country. This research was conducted to find solutions to developing problems and find out the study of norms in Cassation Decision Number: 1 K / Pdt / 2021. The problem of buying and selling land that raises disputes is quite widely experienced by the community, related to taxes and forgery of both identity and certificates, especially in areas where the security system is inadequate. This also triggers a dispute in the form of overlapping certificates, because this overlap is only known if one party feels aggrieved. Theoretically, this research can help provide information about legal protection for parties due to the issuance of overlapping land certificates, as well as legal rules governing legal protection for parties due to the issuance of overlapping land certificates and become one of the contributions of academic thinking to develop legal science, especially business law, land law and land registration. This research can contribute to the addition of knowledge in the study of civil law studies, especially business law, land law and land registration can provide input and consideration for taking policies, especially those related to land law and land registration.